Factores que intervienen en la calidad de vida docente durante la pandemia del COVID-19 - Santana, Leni de Lima; Ramos, Tangriane Hainiski; Ziesemer, Nadine De Biagi; Carvalho Edivane Pedrolo, Telma Pelaes de; Pedrolo, Edivane (Universidad de Costa Rica, 2022)
The COVID-19 pandemic, declared by the World Health Organization, in 2020, forced the population to change attitudes and adapt ways of life in all contexts. In the academic scenario, it resulted in the suspension of in-person activities, in the change of teaching methodologies and in the organization of work. Objective: to identify the intervening factors in the quality of life of teachers at a Brazilian federal public educational institution during the pandemic. Method: descriptive study with a qualitative approach carried out with 20 teachers of Basic, Technical and Technological education. Data was collected remotely, from September to December 2020, through semi-structured interviews processed using the Iramuteq® Software. Results: the study showed that the COVID-19 pandemic interfered with the quality of life of the studied population. As negative effects were observed: work overload; difficulties with routine changes and technological adaptations; wear and tear related to the concern with quality and the teaching-learning process and impacts on physical and mental health. As positive factors were identified: family approximation and self-knowledge. Conclusions: the study identified intervening factors in the quality of life of the participants that have a positive and negative impact on the individual, family and professional scope.